Effectiveness Evaluation of Single-Session Socialization on HIV/AIDS Knowledge among Rural Adolescents in East Kalimantan - Fitria Dewi Puspita Anggraini; Mona Zubaidah; Vera Madonna Lumban Toruan; Nur Khoma Fatmawati; Sholichin Sholichin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Indonesia reports approximately 540,000 HIV cases according to UNAIDS data, with rural adolescents experiencing significant knowledge gaps regarding HIV/AIDS transmission and prevention. Educational interventions are crucial for addressing these deficits, particularly in remote areas with limited healthcare information access. This research to evaluate the effectiveness of socialization interventions on HIV/AIDS knowledge among rural adolescents in East Kalimantan, Indonesia. A quasi-experimental pre-post study design was conducted among 47 adolescents aged 10-17 years in Loa Ulung Village, East Kalimantan. The intervention utilized leaflets and interactive two-way discussions covering HIV/AIDS transmission modes and prevention strategies. Data collection employed a validated 10-item questionnaire administered pre- and post-intervention. Statistical analysis included Shapiro-Wilk normality testing and Wilcoxon signed-rank test for non-parametric comparisons. Pre-intervention knowledge scores averaged 7.43 (SD=1.500), increasing to 7.81 (SD=1.715) post-intervention. The Wilcoxon signed-rank test showed no statistically significant difference (p=0.128), with a normalized gain score of 0.14 indicating low effectiveness. Persistent misconceptions included: 63.8% incorrectly believing all HIV-infected individuals develop AIDS, 23.4% thinking HIV transmits through sharing utensils, and 17.0% believing shared toilets cause transmission. Single-session educational interventions demonstrated limited effectiveness in improving HIV/AIDS knowledge among rural adolescents. Future programs should incorporate age-appropriate, interactive methodologies with extended duration and follow-up sessions for optimal outcomes in rural Indonesian settings.